2021
DOI: 10.2147/ijgm.s328842
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pyroptosis-Associated Long Noncoding RNA Signature to Predict the Prognosis of Patients with Colorectal Cancer

Abstract: Purpose Pyroptosis plays an important role in tumor progression. However, there is no pyroptosis-associated long noncoding RNA (lncRNA) signature to predict the prognosis of patients with colorectal cancer (CRC). Materials and Methods The RNA sequencing data (RNA-seq) and corresponding clinical information relating to CRC patients were obtained from the Cancer Genome Atlas (TCGA) database and the GSE39582 dataset. Univariate Cox regression analysis was used to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Recent studies suggest that the PRLS is satisfactory in predicting the prognosis of several cancers. [ 21 , 23 , 24 , 40 ] These studies provide new clues for further research on the role of PRlncRNAs in cancer.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recent studies suggest that the PRLS is satisfactory in predicting the prognosis of several cancers. [ 21 , 23 , 24 , 40 ] These studies provide new clues for further research on the role of PRlncRNAs in cancer.…”
Section: Discussionmentioning
confidence: 94%
“…Previous evidence has found that PRlncRNAs are linked to tumor progression, prognosis, and immune status. [21][22][23][24] However, little is known about the function and mechanism of these small molecules in glioma.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that lncRNAs can mediate cellular pyroptosis through certain mechanisms and further act on cancer cells. Many investigations have been conducted to establish the signature of PRlncRNAs to predict the prognosis of tumor patients in breast ( Lv et al, 2021 ; Ping et al, 2021 ), ovarian ( Tan et al, 2021 ), melanoma ( Wu L. et al, 2021 ), lung ( Lin et al, 2021 ), endometrial ( Chen et al, 2021 ), liver cancers ( Wu Z. H. et al, 2021 ) etc., but they have rarely been found in GC. Therefore, we started to establish a validated PRlncRNAs biomarker to predict the survival status and treatment outcome of GC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The risk signature performed better in the prediction of one-year OS. Sijun Chen et al [ 85 ] developed a prognostic signature of four pyroptosis-related lncRNAs in CRC. Pyroptosis is a form of inflammatory cell death triggered by inflammasomes [ 86 ].…”
Section: Elfn1-as1 Clinical Implicationmentioning
confidence: 99%